Non-Contact ECG Sensing Employing Gradiometer Electrodes - Peng, GuoChen (2012)
Noncontact, capacitive electrocardiogram (ECG) measurements are complicated by motion artifacts from the relative movement between the ECG electrodes and the subject. To compensate for such motion we propose to employ first and second order gradiometer electrode designs. A MATLAB-based simulation tool to enable assessment of different electrode configurations and placements on human subjects has been developed to guide the refinement of electrode designs. Experimental measurements of the sensitivity, motion artifact cancellation, and common mode rejection for various prototype designs were conducted with human subjects. Second order gradiometer electrode designs appear to give the best performance as measured by signal to noise plus distortion ratio. Finally, both gradiometer designs were compared with standard ECG recording methods and showed less than 1% beat detection mismatch employing an open source beat detection algorithm.